PENGEMBANGAN BAHAN AJAR FLIPBOOK BERBASIS HEYZINE MATERI GAYA KELAS IV SD - Rahayu, Suci Indah; Kartono, Kartono; Halidjah, Siti (Universitas Tanjungpura, 2025)
This research aims to develop a practical flipbook learning resource for the IPAS (Science and Social Studies) subject on the topic